2017
DOI: 10.4103/jispcd.jispcd_372_17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral health education on oral health knowledge of private school children in Riyadh city, Saudi Arabia

Abstract: Aims and Objectives:To assess the early effect of oral health education on oral health knowledge of primary and intermediate school students of private schools by utilizing pre/post questionnaires data from oral health educational projects in Riyadh city, Saudi Arabia. Second, to examine topic-specific knowledge differences between genders, nationalities, and educational levels of the students.Materials and Methods:Cross-sectional oral health educational data of private school students (n = 1279) in primary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…However, study findings showed that primary school students in rural areas exhibited a high level of knowledge in three areas of oral health with correct responses ranging from 80.2% to 81.1%. Almost more than 80.6% of students were knowledgeable about the purpose of toothbrushing, which is in line with 81.6% of private school children in Riyadh, 19 96.3% in Makkah, 25 83% in India. 26 Soft drinks containing acids and sugars have both acidogenic and cariogenic properties.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However, study findings showed that primary school students in rural areas exhibited a high level of knowledge in three areas of oral health with correct responses ranging from 80.2% to 81.1%. Almost more than 80.6% of students were knowledgeable about the purpose of toothbrushing, which is in line with 81.6% of private school children in Riyadh, 19 96.3% in Makkah, 25 83% in India. 26 Soft drinks containing acids and sugars have both acidogenic and cariogenic properties.…”
Section: Discussionsupporting
confidence: 56%
“…doi:10.4103/jispcd.JISPCD_372_17. 19 Available from: https://www.jispcd.org/article.asp?issn=2231-0762;year=2017;volume=7;issue=9;spage=186;epage=193;aulast=Al . Copyright: © 2017 Journal of International Society of Preventive and Community Dentistry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies were carried out in single-gender schools, one in a boys' school 15 and two in a girls' school. 16,17 Twenty-nine of the schools included in the review were public schools; with two private schools 18,19 and two in private and government-run schools. 20,21 The majority of the studies were carried out in urban schools typically based in capital and large cities; only three [22][23][24] were based in rural areas.…”
Section: Key Findingsmentioning
confidence: 99%